Surgical Outcomes in Patients with Toe Walking after Percutaneous Myofasciotomy: Cohort Study - David Pomarino; Bastian Fregien; Alexandr Ya. Nazarkin; Kevin Rostasy; Anna A. Emelina (Вопросы современной педиатрии)
Background. The main method of surgical treatment of toe walking is Achilles tendon extension, which is associated with the risk of excessive correction, tendon rupture, its poor blood supply, plantar flexion deformity. Another alternative is minimally invasive technique, myofasciotomy.Objective. The aim of the study is to study the results of percutaneous myofasciotomy in patients with idiopathic toe walking with severe foot deformity and with no effect of conservative therapy.Methods. The study included data (medical records) from patients with idiopathic toe walking who underwent Ulzibat percutaneous myofasciotomy. We have evaluated the frequency of persistence (recurrence) of toe walking on the next day and 12 months after surgery among all the treatment outcomes. Additionally, the range of motions in ankle joint, the presence of foot deformities, parental satisfaction with surgery results, as well as the number of postoperative complications were analyzed.Results. Percutaneous myofasciotomy was performed in 50 children (11 females) with median age of 13 (10; 16) years during the study period. There were no cases of toe walking on the next day after surgery. Recurrence of toe walking was revealed in 3 (6%) patients within 12 months after surgery. Dorsiflexion rates reached ≥ 10 degrees in all patients at evaluating foot mobility on the next day after surgery and 12 months later. The only revealed surgical treatment complication was postoperative hematoma in 10 (20%) patients. Parents of 3 (6%) children (all with recurrent toe walking) were dissatisfied with surgery results.Conclusion. Ulzibat percutaneous myofasciotomy has shown high efficacy and relative safety in the treatment of patients with idiopathic toe walking.